Characterization of plasma-derived small extracellular vesicle miRNA and protein cargo in hereditary angioedema - Linda Hofmann; Robin Lochbaum; Lutz Schütt; Ralph Röth; Stefanie Schmitteckert; Barbara Wollenberg; Thomas K. Hoffmann; Cornelia Brunner; Jens Greve; Janina Hahn; Marie-Nicole Theodoraki (Extracellular Vesicle)
Hereditary angioedema (HAE) is an inherited disorder causing attacks of subcutaneous tissue or mucosa swelling. The disease burden and attack frequencies vary significantly among patients. This is the first pilot study investigating small extracellular vesicles (sEV) as potential disease modulators in HAE.Plasma-derived sEVs from HAE patients and healthy donors (HD) were thoroughly characterized by Western blot, transmission electron microscopy, nanoparticle tracking and bead-based flow cytometry. The miRNA content of sEVs was examined by nCounter technology and used to predict sEV-based pathomechanisms in silico. All sEV readouts were analyzed regarding HAE-related changes and associations with clinical parameters and attack frequency.Total sEV protein levels were elevated in HAE patients compared to HD. In HAE patients, lower levels of sEVs carrying CD8, CD209, CD81, CD24 and CD44 were measured. sEV miRNA profiling revealed 84 HAE-exclusive and 30 significantly HAE-upregulated candidates. Core hubs of their predicted interaction networks were AGO2, VEGF, RGS5, MTA1, IFG1 and BAX. A set of 12 and 36 sEV miRNAs were restricted to patients with absent attacks or patients with present attacks during prophylactic therapy, respectively.sEVs, especially sEV miRNAs, could contribute to disease pathogenesis and differential attack frequencies. They emerged as disease modulators in HAE and require further study to reveal underlying mechanisms.